Just William - Crompton, Richmal, 1890-; Henry, Thomas (London : MacMillan Children's Books, 2010)
William does odd things--trains rats, kidnaps babies, runs a circus, manages a sweet shop, and falls in love.
3-6.
Keywords: Humorous stories; Humorous fiction